Controlling behaviors in couple relationships in the digital age : acceptability of gender violence, sexism, and myths about romantic love - Sánchez-Hernández, M. Dolores, (Colegio Oficial de Psicólogos de Madrid, 2020)
Young people have incorporated information and communication technology (ICT) and its influence on socialization as a new instrument to exercise controlling behaviors in their relationships. The present research aims to analyse the influence of some variables that affect social perception of those controlling behaviors, such as the adopted role on the scene (i.e., protagonist vs. observer) and means of control that is used (i.e., face-to-face vs. WhatsApp) while considering the effect of attitudinal variables: acceptability of intimate partner violence against women (IPVAW), ambivalent sexism, and myths about romantic love. Two studies were implemented: Study 1 included women (n = 224) and Study 2 included men (n = 120), all of them college students. The main results revealed that both women and men perceive controlling behaviors amongst other peer couples; however, few of them recognize suffering or the exercise of these behaviors within their relationships. In addition, data pointed out the adopted role on the scene and the ideological variables (ambivalent sexism, acceptability of IPVAW, and myths about romantic love) that influenced social perception of dating violence; however, there was no influence of means of control. This research contributes to the previous literature, evidencing that controlling behaviors through technological means are accepted and normalized among young people. Additionally, it shows novel data about young peoples social perception of controlling behaviors in their relationships, depending on whether they adopt the role of observer or the role of protagonist in a violent situation.